THE DYNAMICS OF PALM OIL REGULATION AND POLICY IN INDONESIA: A LITERATURE REVIEW ON THE RELATIONSHIP BETWEEN LOCAL REGULATIONS, ENVIRONMENTAL GOVERNANCE, AND SUSTAINABILITY EFFORTS FROM A SUSTAINABLE DEVELOPMENT PERSPECTIVE - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This article analyses the dynamics of palm oil regulation and policy in Indonesia through a literature review, focusing on the relationship between local regulations, environmental governance, and sustainability efforts from a sustainable development perspective. The study shows that national regulations, particularly through the Indonesian Sustainable Palm Oil (ISPO) and various environmental instruments, provide an important normative framework, but their effectiveness is highly dependent on how local regulations in provinces and districts/cities translate these norms into plantation and environmental management practices. Regulatory fragmentation between the central and regional governments, weak law enforcement, and uncertainty in the certification process for smallholders often reduce the potential contribution of the palm oil sector to sustainable development. From an environmental governance perspective, efforts towards sustainable palm oil in Indonesia still face significant challenges, particularly in controlling the impact of plantation expansion on deforestation, biodiversity loss, and greenhouse gas emissions. Although there are already waste management policies and the application of circular economy principles, the implementation of these regulations varies at the national and regional levels, depending on institutional capacity, technology availability, and the political will of local governments. On the other hand, multi-stakeholder collaborations, such as the Indonesian Sustainable Palm Oil Communication Forum (FoKSBI) and the National Action Plan for Sustainable Palm Oil (NASPO), show potential for strengthening environmental governance and supporting the achievement of the Sustainable Development Goals (SDGs). Overall, the relationship between local regulations, environmental governance, and palm oil sustainability efforts shows that this sector can contribute positively to sustainable development if national and local regulations are managed in a harmonious and inclusive manner. Strengthening environmental governance, harmonising regulations between the central and regional governments, and increasing institutional capacity are key to ensuring that palm oil development in Indonesia not only boosts economic growth but also protects the environment and improves community welfare. Thus, the dynamics of palm oil regulations and policies in Indonesia reflect the transformation of sector governance from an expansive approach to a more sustainable and inclusive one.